PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA PEMERINTAH KABUPATEN PATI - Ahmad Rudi Yulianto; Osmad Muthaher (Tirtayasa Ekonomika, 2019)
The purpose of this study is to knowing the effect of clarity of budget targets, effectiveness of accounting controlsand reporting systems on the performance accountability of government agencies in Semarang city. This study took a sample with convenience sampling techniques in 24 service offices of semarang city with multiple linear regression analysis method. Based on the results of the analysis it can be concluded that the variables of budget target clarity significantly influence the performance accountability of government agencies, the effectiveness of accounting control variables have a significant effect on the performance accountability of government agencies and the reporting system has a significant effect on the performance accountability of government agencies.